The Effect of the ERM on Participating Economies - Bayoumi, Tamim (IMF Working Papers; Working Paper ;, 1991)
The effect of membership of the ERM on macroeconomic performance is analyzed using vector autoregression techniques. The results indicate that while the ERM has had little effect on the nature of the shocks hitting the economies, it has had a significant effect on the response of member countries to these shocks. In addition, long-time members of the ERM have significantly more correlated shocks than other countries. These results conform to the thesis that the ERM represents a move by countries with relatively similar underlying shocks to coordinate macroeconomic policy.